(untitled) (Global Journal of Medical Research, 2021)
As we know that pain is the most common reason for which a patient takes medicine. Pain is not a single entity but may be classified as nociceptive pain, inflammatory pain, and neuropathic pain. Nociceptive pain such pain can be healed or cured by using NSAIDs and other analgesics. Neuropathic pain is caused by the direct lesion on the neuron or damage or dysfunction of peripheral or central neurons. Minor neuropathic can cured automatically because peripheral nervous systems neuron surrounded by Schwann cell which promotes the healing of neurons but CNS neurons don’t have Schwan cell they are covered with oligodendrocytes which don’t have self healing property so pain mediated through CNS are generally chronic. Even the smallest stimulation results in spontaneous intense pain after that it gets transformed into chronic pain syndrome which is difficult to treat.In chronic pain syndrome, plastic changes occur in nociceptive neurons which cant be reversed by pharmacological treatment. In this review, we have discussed the core pathophysiology of neuropathic pain and advances in it to date.